Pemanfaatan Game Edukasi Dalam Pembelajaran Akidah Akhlak Di Sd - Muhammad Miftahuddin; Rangga Azyan; Tasliya Bilqisth Sholiha; Rd.Ilmi Syu’batul Alam; Fiqra Muhamad Nazib (Advances In Education Journal, 2025)
This study investigates the use of educational games to enchance Akidah Akhlak learning in elementary schools. Using a Systematic Literature Review (SLR) method, 5 selected articles were analyzed to examine implementation, implications, and evaluations of game-based learning. The findings reveal that educational games, such as Kahoot and Wordwall, effectively increase students' motivation, engagement, and understanding of Akidah Akhlak concepts. These games create an interactive and enjoyable learning experience that supports various learning styles and promotes character development. However, challenges include dependence on technology, distractions, and limited access to resources, particularly in underprivileged areas. The study emphasizes the need for teachers to receive adequate training to select and integrate high-quality educational games effectively. Overall,  educational games have a positive impact on learning outcomes serve as an innovative and promising tool to improve students’ moral education, foster character building, and enhance learning outcomes in Akidah Akhlak subjects at the elementary school level.